A closer scientific look at foam bitumen. Issue 2 (4th March 2017) - Hailesilassie, Biruk W.; Jerjen, Iwan; Griffa, Michele; Partl, Manfred N.
Abstract : In the asphalt industry, a substantial interest is observed to find possibilities to reduce the production temperature of asphalt mixtures. In the context of this research, new methods for the visualisation of unstable bitumen foam, such as dynamic X-ray radiography, computed tomography (CT) and high-speed camera investigations, have been developed. Moreover, characterisation with empirical methods such as expansion ratio and half-life was determined accurately using ultrasonic measurements. This opens new possibilities to characterise bitumen foam (foaming process) for practical applications. Examination of the foam bitumen stream using a high-speed camera revealed that the foam bitumen contains fragmented pieces of bitumen, which resemble more a liquid than foam. This indicates that the foam is formed afterwards and not, as assumed, within the expansion chamber of the foam generator. In situ thermal imagery of the surface, during the hot foaming process, showed that the temperature distribution depends on the foaming water content (W.C.) and bubble size distribution. Higher W.C. results in more inhomogeneous temperature distribution as compared to lower W.C. (<2 wt%). The dynamic X-radiography results indicated that as the foam decays, the bubble size distribution becomes progressively larger with time for 160°C bitumen temperature. Furthermore, at the beginning of the foam formation, majority of the bubbles is small in cross-section size (0.2–10 mm 2 ). At a later stage, the bubbles become polydisperse. Moreover, theoretical investigations based on the 3D X-ray CT scan data set of bubble merging show that the disjoining pressure increases as the foam film gets thinner with time and finally undergoes rupture. The speed of the bubbles also increases with time when the bubbles are getting closer to each other.